Międzynarodowa współpraca naukowa w rozwoju regionu górnej Noteci - Kulikowski, Roman; Albegov, Murat (Wydział Prawa i Administracji UAM, 1979)
Scentific co-operation between the International Institute for Applied Systems Analysis and the Institute for Systems Research of the Polish Academy of Sciences on perspectives of development of the Upper Noteć Region was started in 1978. Elaboration of a modern methodology of projects of region supplying with water is the basic goal of the research. The article deals with research problems, enclosed in the agreement on co-operation, with effects that have been obtained up to the present and with projects for the future. The research carried on encompasses elaboration of 1) model of industry and agriculture development in a region, and 2) system of models for integrated regional development in relation to development of the whole economy. The system will be containing following models: a) settlements, migration, services, b) health service, c) water resources development and environment protection, and d) region administration. A system of models constructed for the Upper Noteć project can be divided into: models of economic effects, models of water, system development and models of water system ad ministration.. The elaboration of a regional model of economic effects cannot be accomplished when socio-economic and environmenial factors neglected. Elaboration of a proper employment and rural-to- urban migration models, as well as inter-voivodeship migration models is the most important task. In the group of models concerning water system development an economic appraisal of well-founded request for water in the examined region is of fundamental importance for determination of an investment scale. This class of models makes difficulties most of all from the computational point of view since it requires optimization of non-linear functions of many variables in the presence of limitations. The third group of models is connected with steering water system in so called real time. Strategies of steering water resources are to be elaborated in consideration of random fluctuations of supply and demand for water a necessity is emerging here for a system optimalization under stochastic conditions. The end of the research work on development of the Upper Noteć Region is foreseen for the year 1980.
International Scientific Co-operation for a Development of the Upper Noteć Region